Perancangan Sistem Informasi Warga Tingkat RT Berbasis Website Dengan Metode Extreme Programming - Abyghail Shiddiq; Entis Sutrisna (CV. Multi Kreasi Media, 2023)
To increase the use of technology and information in terms of managing citizen administration, making citizen complaint tickets, managing data on residents' contributions to making monthly dues reports on a housing estate have an important role. Bumi Mentari housing Depok Bojongsari. Currently, we do not have a system that can manage citizen data, administrative data, and contribution data. All data still uses the manual method, which is recorded on paper or in a special book that is vulnerable to loss or damage and still causes many problems such as data on residents who have not paid dues in the previous month are lost or not stored properly so that the data and needs received by The head of the RT are not fulfilled every month, the grouping of citizen data is still recorded manually, which takes time to group it. In designing the RT level information system using the Extreme Programming model, this Extreme Programming model was chosen because in its implementation it is very flexible and fast in making the application, the stages themselves include planning, design, coding which includes refactoring in it and finally testing. The design of this RT Level citizen information system is website-based and built with the PHP programming language and assisted by the MYSQL database.